Central Sleep Apnea Syndrome Can Complicate Neuromyelitis Optica Spectrum Disorder: A Case Report - Morelli, Céline; Aeby, Alec; Scaillet, Sonia; Boitsios, Grammatina; Vens, Daphné; Prigogine, Cynthia; Biarent, Dominique; Vicinanza, Alfredo (Frontiers in Pediatrics, 2020)
Neuromyelitis optica spectrum disorder is a rare, relapsing autoimmune disease of the central nervous system. Various initial presentations can delay diagnosis and treatment. A 14-year-old girl was admitted to the emergency department owing to respiratory insufficiency. Repeated history-taking and neuroimaging revealed an area postrema syndrome. A diagnosis of neuromyelitis optica spectrum disorder with positive aquaporin-4 antibodies has finally been established. The patient improved significantly with immunosuppressive therapy. However, her 3-year follow-up showed persisting sleep-disordered breathing requiring nocturnal bilevel positive airway pressure therapy. We report an original case of NMOSD leading to persistent central sleep apnea syndrome.